Computational Insights into the Dual Inhibition of PfATP6 and PfCRT by Bioactive Compounds from Spatholobus littoralis Hassk. - Wahyuningtias, Dita Sheilla Putri; Putra, Oktavian Arya; Turnip, Laurens Frestasya A.; Ananda, Putu Desy Sagita; Wibowo, Syahputra; Wisynu Kusuma Wardhani, Bantari (Fakultas Kedokteran Universitas Sriwijaya, 2025)
The current study examined the antimalarial activity of bioactive compounds extracted from Spatholobus littoralis Hassk. (bajakah wood) by an in-silico approach targeting the Plasmodium falciparum PfCRT and PfATP6 receptors. A total of forty-six phytochemicals were subjected to screening, resulting in the selection of six compounds based on bioactivity prediction, ADMET profiling, and molecular docking analyses. Ramachandran plots were used to check the accuracy of the model, which showed that the protein structures were reliable. Milbemycin A4-oxime exhibited the most significant binding affinity (−9.6 kcal/mol for PfCRT and −9.9 kcal/mol for PfATP6). These findings are comparable to or slightly better than those observed for artemisinin in this in silico model. These findings are preliminary and require further experiment. The molecule exhibited persistent interactions and favorable pharmacokinetic properties, indicating its potential use as a multitarget inhibitor. Quercetin and 8-O-methylretusin had significant efficacy. These results underscore the potential of S. littoralis metabolites, especially Milbemycin A4-oxime, as candidates for antimalarial drug development; however, additional in vitro and in vivo validation is necessary to establish efficacy and safety.